Menjaga Eksistensi Dharma Boutique Roastery: Eksplorasi Strategi Komunikasi Pemasaran Pabrik Kopi Tertua di Semarang - Arni Ernawati; Erna Zuni Astuti; Diah Soelistyowati (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
Coffee was a leading commodity when the colonizers came to Indonesia, one of which was robusta coffee. The best coffee varieties are produced in local factories, such as Dharma Boutique Roastery.Departing from efforts to survive in business in the midst of the times, this research focuses on how the marketing communication strategy of the Dharma Boutique Roastery coffee factory can still exist in the era of the development of modern coffee factories. This research is a qualitative study with data collection techniques of observation and interviews with Dharma Boutique Roastery owners and employees. The research indicates that Dharma Boutique Roastery is the oldest coffee factory in Semarang which was founded in 1915 by Tan Tiong Ie. Located in the Semarang Chinatown complex, this coffee factory still exists today and is a supplier of Indonesian export coffee as much as 60%. In the face of an increasingly competitive coffee market, Dharma Boutique Roastery can increase its presence with effective marketing communication strategies, such as increasing presence on social media, offering unique experiences, and improving product quality. Tourists can enjoy stories and coffee at Semarang Chinatown which stores the history of Indonesian coffee.